Pengetahuan dan Pelaksanaan Shalat Siswa Sekolah Dasar - Hj. Zahera Sy (Universitas Negeri Malang, 2016)
The purpose of the research was to know how much the fifth year students of elementary schools know about prayers in Islam and their praying activities. The sample included 240 fifth graders of SDN in Palembang. Data were collected using test, questionnaire, and observation. The result indicates that the knowledge of the fifth year student of SD Negeri Palembang about prayer falls into insuccifient category. The methods used by the teacher were lecture, dialog, tasks, and practice. The praying activities of the students fall into worse category